2013
DOI: 10.1016/j.jtcvs.2012.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Putting the record straight on aprotinin as safe and effective: Results from a mixed treatment meta-analysis of trials of aprotinin

Abstract: This mixed treatment comparisons meta-analysis demonstrates no increased mortality risk with aprotinin versus other antifibrinolytic agents. All agents were superior to placebo in reducing reexploration for bleeding after adult cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 16 publications
0
33
0
6
Order By: Relevance
“…However, the trial was stopped prematurely because of an increase in mortality in the aprotinin group. 35 Subsequent studies found it safe, 36 resulting in a reintroduction in some instances. Taking the elective and safe nature of OS into account and that alternative hemostatic adjuncts are available, these should be the first-choice drugs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the trial was stopped prematurely because of an increase in mortality in the aprotinin group. 35 Subsequent studies found it safe, 36 resulting in a reintroduction in some instances. Taking the elective and safe nature of OS into account and that alternative hemostatic adjuncts are available, these should be the first-choice drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Aprotinin functions via the same mechanism as PAI-1, while lysine analogs, such as 6-aminocaproic acid and TXA, block the lysine-binding sites on plasminogen, thereby preventing the activation of plasmin and fibrin clot-degradation (19). The USA Food and Drug Administration has removed aprotinin, a bovine product, from the market due to statistical associations with renal failure, cerebrovascular events and mortality, without significantly stronger antifibrinolytic effects over other medications within the class (23)(24)(25). As a natural constituent of blood, VLHL PAI-1 may be free of side effects in addition to being an efficient antifibrinolytic agent.…”
Section: Discussionmentioning
confidence: 99%
“…En cirugía cardíaca, un metaanálisis publicado en 2009 mostraba que el uso de APT se asociaba con un incremento de la mortalidad con respecto al ATX 41 , pero 2 metaanálisis recientes han sembrado dudas sobre la supuesta mayor toxicidad de la APT en comparación con los análo-gos de la lisina 42,43 . Finalmente, un cuarto metaanálisis de estudios aleatorizados y observacionales encuentra que, en comparación con análogos de la lisina, la APT puede asociarse con un mayor riesgo de mortalidad en cirugía cardíaca de riesgo bajo e intermedio, pero parece no afectar la mortalidad en cirugía cardíaca de alto riesgo 44 .…”
Section: Seguridad De La Aprotininaunclassified